THE USE OF COMPETITION AS A COMMUNICATION STRATEGY (To Increase Engagement as a Form of Brand Awareness about Local Skateboarding Shoes in Jabodetabek Area) - Florenzia Shafira Esmeralda Riswanto; Anindita Alifiani Prianto; Alexander Mamby Aruan (Profetik: Jurnal Komunikasi, 2020)
Abstract. The rapid development of skateboarding in Indonesia serves as a business opportunity for local entrepreneurs. Although the skateboard market in Indonesia is classified as a segmented market, but it is still a promising business. Local skateboarding shoes brand developed quite rapidly along with the development of skateboarding sports in Indonesia, this is portrayed by the high level of enthusiasm by the society who starting to play skateboard, the high amount of local skateboarding communities appears in Jabodetabek area and plentiful skateboarding events and competitions. The result of this research shows that there has been a lot of skateboarding competition in Indonesia which has been used as a communication strategy. Competitions are considered good and effective for local skateboarding shoes brand to increase engagement as a form of brand awareness, because they can take part either as the supporting element or as the skateboarding competition organizer. Besides, it also can bring a positive impression to the brands itself. In addition, the competitions held offline needs to be supported by online activities and the source includes education elements. Berlo’s Communication Model (SMCR) explains that when using a competition, it needs to be based on the communication skills, the understanding of social and cultural systems of the source and the receiver to the message that can be felt by the human five senses which will increase the success of delivering messages from the source to the receiver. The methodology of this research is qualitative and the instrument used to collect data involves interviews.Abstrak. Pesatnya perkembangan skateboard di Indonesia menjadi peluang bisnis bagi para pengusaha lokal. Meskipun pasar skateboard di Indonesia tergolong sebagai pasar yang tersegmentasi, namun bisnis pada industri ini tetap menjanjikan. Merek sepatu skateboard lokal berkembang cukup pesat seiring dengan perkembangan olahraga skateboard di Indonesia, hal ini dapat dilihat dari tingginya antusiasme masyarakat yang mulai bermain skateboard, jumlah komunitas skateboard lokal yang bermunculan di daerah Jabodetabek, hingga banyaknya acara dan kompetisi bertajuk skateboard. Hasil penelitian ini menunjukkan bahwa terdapat banyak kompetisi skateboard di Indonesia yang telah digunakan sebagai strategi komunikasi. Kompetisi dianggap baik dan efektif bagi para merek sepatu skateboard lokal untuk meningkatkan keterlibatan masyarakat sebagai bentuk kesadaran merek, karena mereka dapat berperan sebagai elemen pendukung atau penyelenggara kompetisi skateboard. Kompetisi juga dapat memberikan kesan positif bagi merek itu sendiri. Selain itu, kompetisi yang diadakan secara offline perlu didukung oleh aktivitas online dan mencakup unsur edukasi. Model Komunikasi Berlo (SMCR) menjelaskan bahwa ketika menggunakan sebuah kompetisi, perlu didasarkan pada keterampilan komunikasi, pemahaman csistem sosial dan budaya dari sumber dan penerima pesan yang kemudian dapat dirasakan oleh panca indera manusia untuk meningkatkan keberhasilan penyampaian pesan dari sumber ke penerima. Metode penelitian ini adalah kualitatif dan instrumen yang digunakan untuk mengumpulkan data adalah wawancara.